Evaluation of Rangeland Forage Improvement through Bush Controlling Techniques in Lowland Areas of Borana Zone, Southern Ethiopia - Kebeto, Feyissa Desiso; Minyilu, Yonas Aseffa (PT FORMOSA CENDEKIA GLOBAL, 2025)
A study was conducted in the Dirre and Yabello districts of Borana rangelands. The districts were selected purposively based on the severity of bush encroachments. A total of 5.4 hectares of bush encroached rangeland (2.7 ha in each district) was selected. The experiments had six treatments; 0% thinning (T 1),0% thinning Plus Fire (T2), 50% Thinning (T3), 50% thinning plus Fire (T4), thinning at 75% intensity only (T5)and thinning at 75% intensity and application of fire(T6) replicated three times. The treatments were applied on 18 different plots with an area of 30mx50m each. The collected data were analyzed using SAS software. The result showed that thinning the bush at 50% and 75% intensity combined with prescribed fire enhanced forage production while negatively influenced invasive woody shrubs and therefore would sustain the original savannas in Borana rangelands.